Historical Analysis of Islamic Philosophical Thought According to Imam Al-Ghazali - Sugih Nugraha; Neneng Suwerma; Didik Himmawan (Konsultan Jurnal Ilmiah Indonesia, 2024)
Imam Al-Ghazali is a major figure in the history of Islamic thought, famous for his controversial works such as